Relevance of Amorphous and Amyloid-Like Aggregates of the p53 Core Domain to Loss of its DNA-Binding Activity - Hibino, Emi; Tenno, Takeshi; Hiroaki, Hidekazu (Frontiers in Molecular Biosciences, 2022)
The anti-oncogenic protein p53 is a transcription factor that prevents tumorigenesis by inducing gene repair proteins or apoptosis under DNA damage. Since the DNA-binding domain of p53 (p53C) is aggregation-prone, the anti-oncogenic function of p53 is often lost in cancer cells. This tendency is rather severe in some tumor-related p53 mutants, such as R175H. In this study, we examined the effect of salts, including KCl and sugars, on the aggregation of p53C by monitoring two distinct aggregates: amorphous-like and amyloid-like. The amorphous aggregates are detectable with 8-(phenylamino)-1-naphthalenesulfonic acid (ANS) fluorescence, whereas the amyloid aggregates are sensitive to thioflavin-T (ThT) fluorescence. We found that KCl inhibited the formation of amorphous aggregates but promoted the formation of amyloid aggregates in a p53C R175H mutant. The salts exhibited different effects against the wild-type and R175H mutants of p53C. However, the ratio of ANS/ThT fluorescence for the wild-type and R175H mutant remained constant. KCl also suppressed the structural transition and loss of the DNA-binding function of p53C. These observations indicate the existence of multiple steps of p53C aggregation, probably coupled with the dissociation of Zn. Notably, amorphous aggregates and amyloid aggregates have distinct properties that could be discriminated by various small additives upon aggregation.